Liver Organoids Generated from Mice with Necrotizing Enterocolitis Have Reduced Regenerative Capacity - Miyake, Hiromu; Lee, Carol; Seo, Shogo; Li, Bo; Pierro, Agostino (European Journal of Pediatric Surgery, 2020)
Introduction Necrotizing enterocolitis (NEC) is one of the most severe gastrointestinal diseases in infancy. NEC can cause metabolic derangements, multi-organ injury including severe liver damage. The mechanism leading to hepatic damage in NEC remains unclear. The aim of this study is to establish and characterize liver organoids from NEC mice.Materials and Methods Following ethical approval (#44032), we induced experimental NEC from postnatal day 5 (P5) to P9 using C57BL/6 mice pups. NEC was induced by gavage formula feeding, gavage lipopolysaccharide (LPS) administration, and hypoxia. Breastfed pups were used as control. On P9, NEC and control pups were sacrificed and liver tissue was harvested and organoids were generated. Organoid size was recorded daily (day 2–4) by measuring their surface area and organoid growth was calculated. RNA was extracted on day 4 after liver organoid generation.Results Organoid growth rate was significantly lower in NEC liver organoids compared to control liver organoids. mRNA expression of liver progenitor cells markers of LGR5 and SOX9 was lower in NEC liver organoids compared to control liver organoids. Similarly, expression of proliferation markers of Ki67 and PCNA was lower in NEC liver organoids.Conclusion We report a novel technique to generate liver organoids during NEC. These organoids are characterized by reduced progenitor cells, reduced proliferation, and overall impaired regenerative capacity. Liver progenitor cells are important targets to prevent liver damage in NEC and promote recovery.
Keywords: necrotizing enterocolitis; liver injury; organoids; regeneration